1998
DOI: 10.1177/002221949803100104
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology for Postsecondary Students with Learning Disabilities

Abstract: The number of postsecondary students with learning disabilities has increased dramatically over the last several years. This increase, coupled with federal legislation mandating "academic adjustments" for students with disabilities, has prompted the development of postsecondary learning disability support service programs. One support service that has begun to attract considerable attention is assistive technology. The purpose of this article is to provide an overview of assistive technology as it relates to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 19 publications
2
54
0
6
Order By: Relevance
“…In the face of this research, the field needs extensive investigation of the effectiveness of AT in postsecondary education settings. (Li & Hamel, 2003;Raskind & Higgins, 2003;Zabala & Carl, 2005). Burgstahler (2002) contended that in order for students with disabilities to pursue postsecondary education programs, they must have knowledge and skills in use of various types of technology that includes access to websites, Internet-based distance learning courses, instructional software, and scientific equipment.…”
Section: Assistive Technologymentioning
confidence: 99%
“…In the face of this research, the field needs extensive investigation of the effectiveness of AT in postsecondary education settings. (Li & Hamel, 2003;Raskind & Higgins, 2003;Zabala & Carl, 2005). Burgstahler (2002) contended that in order for students with disabilities to pursue postsecondary education programs, they must have knowledge and skills in use of various types of technology that includes access to websites, Internet-based distance learning courses, instructional software, and scientific equipment.…”
Section: Assistive Technologymentioning
confidence: 99%
“…Researchers and teachers in the field of special education have made efforts to incorporate technology into math curricula for students with learning difficulties to improve their results effectively and efficiently (Anderson-Inman, Knox-Quinn, & Horney, 1996;Ferretti & Okolo, 1996, Raskind & Higgins, 1998Torgesen & Barker, 1995, Woodward & Carnine, 1993Robinson, DePascale, & Roberts, 1989). As it is expected, students' effort is also required.…”
Section: Introductionmentioning
confidence: 99%
“…This tool accesses a dyslexic's listening capability and enables him/her to gain knowledge from an auxiliary source (Shaywitz and Shaywitz 2012). Elkind et al (1993) who studied on computer-based readers found that 70 % of 28 middle school dyslexic students read with greater comprehension when using such readers and concluded (Lazar et al 2007); Leporini and Paternò (2004); Raskind and Higgins (1998) as well as Wies et al (2001) highlight the use of screen reader among people with disabilities which include learning disabilities, blind, and visually impaired. As majority of the normal participants in this study also indicated their strong preference toward this mode, the screen reader is also deemed appropriate for this group of learners.…”
Section: Enhanced Mode: Excellent Satisfaction (Normal Dyslexic)mentioning
confidence: 99%